Housing provision and improvement programmes for low income populations in the developing world. A review of approaches and their significance in the European context - Gałuszka Jakub (Bulletin of Geography. Socio-Economic Series, 2012)
The paper deals with the issue of affordable housing provision for low income populations in the developing countries and its significance in the European context. My goal is to discuss this topic through the analysis of different approaches to household provision and improvement with special focus on the involvement of communities in various upgrading procedures. Separate sections of the paper refer to the most important approaches developed in the 20th and 21st centuries. These include: site and service, slum upgrading, incremental housing and communityled upgrading which are analysed through the prism of several examples coming from various parts of the world.